2009
DOI: 10.1162/jocn.2009.21014
|View full text |Cite
|
Sign up to set email alerts
|

On-line Orthographic Influences on Spoken Language in a Semantic Task

Abstract: Literacy changes the way the brain processes spoken language. Most psycholinguists believe that orthographic effects on spoken language are either strategic or restricted to meta-phonological tasks. We used event-related brain potentials (ERPs) to investigate the locus and the time course of orthographic effects on spoken word recognition in a semantic task. Participants were asked to decide whether a given word belonged to a semantic category (body parts). On no-go trials, words were presented that were eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
4
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 41 publications
10
83
4
1
Order By: Relevance
“…ERP (Event-related potential) data has also provided a productive means of probing time-course effects of literacy on online speech processing. Such studies demonstrate an early influence of orthography during spoken word processing, critically with effects observed in windows prior to points that are classically viewed as the time point of lexical access (Semantic categorisation task: Pattamadilok, Perre, Dufau, & Ziegler, 2009;Lexical decision task: Perre, Midgley, & Ziegler, 2009a;Perre, Pattamadilok, Montant, & Ziegler, 2009b;Perre & Ziegler, 2008). Ziegler and Ferrand (1998) suggest that the mechanisms underlying the effects of orthography on online speech processing are that following literacy training orthographic representations are activated online when processing spoken words and it is such online activation that leads to effects of orthography on speech processing.…”
Section: Changes To Phonological Representations and Literacymentioning
confidence: 96%
“…ERP (Event-related potential) data has also provided a productive means of probing time-course effects of literacy on online speech processing. Such studies demonstrate an early influence of orthography during spoken word processing, critically with effects observed in windows prior to points that are classically viewed as the time point of lexical access (Semantic categorisation task: Pattamadilok, Perre, Dufau, & Ziegler, 2009;Lexical decision task: Perre, Midgley, & Ziegler, 2009a;Perre, Pattamadilok, Montant, & Ziegler, 2009b;Perre & Ziegler, 2008). Ziegler and Ferrand (1998) suggest that the mechanisms underlying the effects of orthography on online speech processing are that following literacy training orthographic representations are activated online when processing spoken words and it is such online activation that leads to effects of orthography on speech processing.…”
Section: Changes To Phonological Representations and Literacymentioning
confidence: 96%
“…Furthermore, orthographic neighborhood density (defined as the number of words that substitute a single letter within the word) also affect spoken word processing, with faster lexical decisions for words with many neighbors than with fewer neighbors (Ziegler, Muneaux, & Grainger, 2003), and the magnitude of the neighborhood effect being modulated by orthographic experience and proficiency. Finally, orthographic effects have emerged even in tasks which do not require a metaphonological analysis or lexical decision, such as when judging whether a spoken word belongs to a particular semantic category (e.g., Pattamadilok, Perre, Dufau, & Ziegler, 2009; see below for a more detailed outline), or when detecting a noise burst in a non-linguistic task (e.g., Perre, Midgley, & Ziegler, 2009). …”
Section: Orthographic Effects In Spoken Word Recognition: Evidence Frmentioning
confidence: 99%
“…Orthographic effects in spoken word recognition can also be explored via electroencephalography (EEG), and it appears that such effect emerge quite rapidly, in a relatively early time window starting around 300 ms after stimuli onset (e.g., Pattamadilok, Perre, Dufau, & Ziegler, 2009;Pattamadilok, Morais, Colin, & Kolinsky, 2014). For instance, Pattamadilok et al (2009) reported an EEG study in which participants pressed a key when a spoken word belonged to a semantic category, and withheld their response otherwise.…”
Section: Orthographic Effects In Spoken Word Recognition: Evidence Frmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, words of different levels of alphabetic regularity can be written (8,9) . There are few studies which establish the relationship between the alterations of the phonological processes among school children with dyslexia and students with good academic performance, although there is a vast literature establishing the relationship between orality and writing (10,11) . Nonetheless, the present study also proposes to employ the phonological alterations severity analysis, already described in the national literature, concerning speech and also writing.…”
Section: Introductionmentioning
confidence: 99%